Prosecutor: the History, Duties, and Responsibilities in Georgia, and Other Foreign Countries - Tkeshelashvili, Shota (Journal of Legal Studies, 2022)
The prosecutor is an individual who on behalf of the Government carries on criminal prosecution against the guilty person and in the court with the mandate of society and supports the State Prosecution. The main aim of the prosecutor is the find out such objective and indisputable evidence, which will help the court to make the right and fair decision. The present article according to the qualitative research method focuses on the history, stages of development, and current functions of the prosecutors.  Based on this, it became clear how effective and productive the prosecutor's participation in the court is and, in general, how independent the prosecutor is in the performance of his or her functions and what are similarities and differences in different countries prosecutor’s independence, roles, and responsibilities. As the study highlighted the International Prosecutor should have exclusively such rights, as investigation and implementation of criminal persecution against specific persons. Apart from these restrictions imposed by the legislation, of course, substantive importance is given to the global situation in the world during the prosecutor's activities.